Body of lies - Johansen, Iris (Random House, Inc, 2002)
When a government official requests her skills at reconstruction to identify an unknown murder victim, forensic sculptor Eve Duncan is drawn into a web of betrayal and murder as she tries to unlock the secrets that someone wants to keep hidden.